ANALISIS LOYALITAS PELANGGAN KOPI KENANGAN (STUDI KASUS PADA KONSUMEN KOPI KENANGAN GENERASI Z DI DKI JAKARTA) - Wahyu Alfiansyah (2023)
This study aims to analyze the factors influencing customer loyalty among Generation Z customers of Kopi Kenangan in DKI Jakarta. The factors examined include product quality, service quality, and sales promotion. The research method employed was non-probability sampling using purposive sampling. A total of 104 respondents who have purchased Kopi Kenangan products in DKI Jakarta at least 3 times were selected as the study sample. Primary data were obtained through the distribution of questionnaires and analyzed using PLS (SmartPLS 3.0) software. The results of the study indicate that product quality has a positive and significant impact on customer loyalty. However, service quality does not have a significant influence on customer loyalty. On the other hand, sales promotion has a positive and significant impact on customer loyalty of Kopi Kenangan Generation Z in DKI Jakarta.